(untitled) - Rafiquzzaman, Mohamed (New York, 1984)
Mohamed Rafiquzzaman's comprehensive new text is a guide to today's hardware and software development aids - the 8, 16, and 32-bit microprocessors, support chips, and microcomputer development systems that have become essential tools for scientists and engineers. Combining theory and applications, the book provides readers with techniques needed to design and develop hardware and software for microcomputer-based applications. In practical and understandable terms, the author provides: a step-by-step procedure for designing applications with a typical microcomputer development system; numerous practical examples, using the Hewlett-Packard 64000 to give a realistic picture of the actual designing process; discussions of the various microcomputer development systems currently in use, emphasizing their common characteristics and principles; laboratory exercises and procedures for hands-on experience; plus a complete overview of microprocessor architecture, programming concepts, and hardware.
Keywords: Thiết kế hệ thống,System design